1988
DOI: 10.1083/jcb.107.5.1853
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic and functional characterization of a vascular addressin involved in lymphocyte homing into peripheral lymph nodes.

Abstract: The tissue localization or "homing" of circulating lymphocytes is directed in part by specialized vessels that define sites of lymphocyte exit from the blood. In peripheral lymph nodes, mucosal lymphoid tissues (Peyer's patches and appendix), and sites of chronic inflammation, for example, lymphocytes leave the blood by adhering to and migrating between those endothelial cells lining postcapillary high endothelial venules (HEV). Functional analyses of lymphocyte interactions with HEV have shown the lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
417
1
2

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 596 publications
(436 citation statements)
references
References 38 publications
16
417
1
2
Order By: Relevance
“…A recent study also indicates, although indirectly, a similar pattern of ␣4␤7 expression on ASC induced by diarrheal disease (35). It is possible that the ␣4␤7 ϩ and L-selectin Ϫ ASC are bound to extravasate through flat-walled venules in the intestinal lamina propria, which constitutively express MAdCAM-1 but only little PLN addressin (8,10,36). ␣4␤7 ϩ and L-selectin ϩ ASC, on the other hand, may leave the circulation and migrate to more organized mucosal lymphoid tissues, such as mesenteric lymph nodes (MLN) and Peyer's patches, whose HEV express both MAd-CAM-1 and PLN addressin (36,37), and to which L-selectindependent homing has been documented (38).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent study also indicates, although indirectly, a similar pattern of ␣4␤7 expression on ASC induced by diarrheal disease (35). It is possible that the ␣4␤7 ϩ and L-selectin Ϫ ASC are bound to extravasate through flat-walled venules in the intestinal lamina propria, which constitutively express MAdCAM-1 but only little PLN addressin (8,10,36). ␣4␤7 ϩ and L-selectin ϩ ASC, on the other hand, may leave the circulation and migrate to more organized mucosal lymphoid tissues, such as mesenteric lymph nodes (MLN) and Peyer's patches, whose HEV express both MAd-CAM-1 and PLN addressin (36,37), and to which L-selectindependent homing has been documented (38).…”
Section: Discussionmentioning
confidence: 87%
“…It is possible that the ␣4␤7 ϩ and L-selectin Ϫ ASC are bound to extravasate through flat-walled venules in the intestinal lamina propria, which constitutively express MAdCAM-1 but only little PLN addressin (8,10,36). ␣4␤7 ϩ and L-selectin ϩ ASC, on the other hand, may leave the circulation and migrate to more organized mucosal lymphoid tissues, such as mesenteric lymph nodes (MLN) and Peyer's patches, whose HEV express both MAd-CAM-1 and PLN addressin (36,37), and to which L-selectindependent homing has been documented (38). In accordance with this notion, our previous studies have shown that MLN harbor large numbers of vaccine-specific ASC after enteric immunization in monkeys (39).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, 2F3 and HECA-452 mAbs detect ␣2,3 sialylation and ␣1,3 fucosylation of lactosamine and do not distinguish between sulfation and nonsulfation. 29,30 On the other hand, MECA-79 needs sulfation of its epitope for proper recognition. 31,32 The best ligands, ie, ligands with highest relative binding affinity toward L-selectin, would possess all these decorations, as shown in lymphatic tissue.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 This is actually a family of glycoproteins, most of which are able to bind L-selectin. In humans only CD34 and podocalyxin have been identified at molecular level among the glycoprotein species reacting with MECA-79.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the MLN drain lymphocytes from the intestine and it was shown that MLN possess features of both mucosal and peripheral lymphoid tissue in terms of lymphocyte trafficking (35,36). In this regard, high endothelial venules in MLN clonally express high levels of both mucosal addressin cell adhesion molecule-1 and peripheral LN addressin which are major mucosal and peripheral LN addressins, respectively (37). Further, mucosal as well as peripheral node cell lines have been shown to bind to high endothelial venules of MLN in vitro (38).…”
Section: Discussionmentioning
confidence: 99%